The authoritarian specter - Altemeyer, Bob (Cambridge, Mass. : Harvard University, 1996)
Introduction: Twenty stories Previous research on right-wing authoritarianism
Studying authoritarianism: Research methodology and methodology research
The personal origins of right-wing authoritarianism
The cognitive behavior of authoritarians
Inconsistency and blindness in the authoritarian mind
Authoritarianism and religion
Sex and the single authoritarian
Dogmatism
Left-wing authoritarianism
The effects of hate literature
The authoritarianism of legislators in North America
Conclusion: A few last words on the subject
Bibliografija
Kazalo
Keywords: autoritarnost; ekstremna desnica; razvoj ličnosti; osobine ličnosti